Thermodynamic study of benzocaine insertion into different lipid bilayers - López Cascales, José Javier (2011)
Despite the general consensus concerning the role played by sodium channels in the molecular mechanism of local anesthetics, the potency of anaesthetic drugs also seems to be related with their solubility in lipid bilayers. In this respect, this work represents a thermodynamic study of benzocaine insertion into lipid bilayers of different compositions by means of molecular dynamics simulation. Thus, the free energy profiles associated with benzocaine insertion into symmetric lipid bilayers composed of different proportions of dipalmitoylphosphatidylcholine and dipalmitoylphosphatidylserine were studied. From the simulation results, a maximum in the free energy (ΔG) profile was measured in the region of the lipid/solution interface. This free energy barrier appears to be very much dependent on the lipid composition of the membrane. On the other hand, the minimum free energy (ΔG) within the bilayer remained almost independent of the lipid composition of the bilayer. By repeating the study at different temperatures, it was seen how the spontaneity of benzocaine insertion into the lipid bilayer is due to an increase in the entropy associated with the process.